Hubungan antara Mutu Pelayanan Kefarmasian dengan Kepuasan Pasien Rawat Jalan di Puskesmas Teling Atas Kota Manado - Kawahe, Monika (UNIVERSITAS SAM RATULANGI, 2015)
Hubungan antara Mutu Pelayanan Kefarmasian dengan Kepuasan Pasien Rawat Jalan di Puskesmas Teling Atas Kota Manado Monika Kawahe1), Chreisye K. F. Mandagi1), Paul A.T Kawatu1) Fakultas Kesehatan Masyarakat Universitas Sam Ratulangi Manado ABSTRACT The demandsof patients andsocietyto theimprovement of the pharmacy services’ quality, requirean extension ofthe old paradigmwhich was oriented tothe product(drugoriented)into the new one,that isoriented tothe patient(patient-oriented) with the philosophy ofpharmaceutical services(pharmaceutical care). Patients’dissatisfactionis cause by the appearance of gap betweenthe patients’ expectationsand performance of thehealth care that is felt while taking the service itself. The Puskesmas (clinic) must keenly determine the needs of the patients or costumers as an effort tomeet the expectationsandincreasesatisfactionwith the providedservices. The aim ofthis research is toanalyzethe relationbetweenthequalityof pharmaceutical services and outpatientssatisfactionat Puskesmas Teling AtasinManado.This research uses analytical survey with a study plan that is stated as Cross Sectional Study, the sample of research is taken by using the Accidental Sampling method with considering the patients who accidentally visit Puskesmas Teling Atas in Manado, with the total amount of 100 respondents. The data has been collected and analyzed by Univariate and Bivariat. Primary data obtained from questionnaires and secondary data collected from Puskesmas’ profile. The statistical test used isChi Square test with the computer application program. The responsiveness of pharmaceutical Services with patients' satisfaction p value = 0.042 is related, the reliability of pharmaceutical services with patients' satisfaction p value = 0.016 is related, the guarantees of pharmaceutical services with patients' satisfaction p value = 0.219 is unrelated, the care of pharmaceutical serviceswith patients’ satisfaction score p value = 0,028 is related, direct evidence of pharmaceutical serviceswith patients' satisfaction p value = 0.044 is related. The result of this research, are: there is a relation between pharmaceutical services, such as: the responsiveness, the reliability, the care, and the direct evidence with the patients’ satisfaction, and there is not a relation between pharmaceutical services and the guarantee of patients’ satisfaction at Puskesmas Teling Atas in Manado. Keywords:The Quality of Pharmaceutical Services, Patients’ Satisfaction. ABSTRAK Tuntutan pasien dan masyarakat akan peningkatan mutu pelayanan kefarmasian, mengharuskan adanya perluasan dari paradigma lama yang berorientasi kepada produk (drug oriented) menjadi paragdima baru yang berorientasi pada pasien (patient oriented) dengan filosofi pelayanan kefarmasian (pharmaceutical care). Ketidakpuasan pasien timbul karena terjadinya kesenjangan antara harapan pasien dengan kinerja layanan kesehatan yang dirasakannya sewaktu menggunakan layanan kesehatan. Pihak Puskesmas perlu secara cermat menentukan kebutuhanpasien/konsumen (pelanggan) sebagai upaya untuk memenuhi harapan dan meningkatkan kepuasan atas pelayanan yang diberikan. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat hubungan antara mutu pelayanan Kefarmasian dengan kepuasan pasien rawat jalan di Puskesmas Teling Atas Kota Manado. Penelitian ymenggunakan metode survei analitik dengan rancangan Cross Sectional Study. Pengambilan sampel menggunakan metode accidenttal sampling dengan mengambil pasien yang kebetulan berkunjung di Puskesmas Teling Atas Kota Manado dengan jumlah responden 100 responden. Data yang telah dikumpulkan dianalisis secara Univariat dan Bivariat. Data primer didapatkan dari kuesioner dan data sekunder di dapatkan dari profil Puskesmas. Uji statistik yang digunakan adalah uji Chi Square dengan program aplikasi komputer. Ketanggapan pelayanan kefarmasian dengan kepuasan pasien nilai p value = 0,042 berhubungan, kehandalan pelayanan kefarmasian dengan kepuasan pasien nilai p value = 0,016 berhubungan, jaminan pelayanan kefarmasian dengan kepuasan pasien nilai p value = 0,219 tidak berhubungan, kepedulian pelayanan kefarmasian dengan kepuasan pasien nilai p value = 0,028 berhubungan, bukti langsung pelayanan kefarmasian dengan kepuasan pasien nilai p value = 0,044 berhubungan. Hasil penelitian menunjukkan adanya hubungan antara pelayanan kefarmasian yaitu ketanggapan, kehandalan, kepedulian, bukti langsung dengan kepuasan pasien di Puskesmas Teling Atas Kota Manado dan tidak adanya hubungan antara pelayanan kefarmasian antara jaminan dengan kepuasan pasien. Kata Kunci:`Mutu Pelayanan Kefarmasian, Kepuasan Pasien.